Karakter Televisi dan Radio yang Relevan - Winda Kustiawan; Sri Tsulatsiah Putri Nabila G; Aisyah Amini Salam; Salima Zarli Lubis; Nurhayati Br. Sembiring; Reydho Febriansyah; Rakhas Djuniardy; M. Zidan Syahrevi (Maktabatun: Jurnal Perpustakaan dan Informasi, 2022)
This journal was created to discuss various techniques from several media sources of information including television and radio. There are several techniques that aim to make us understand how we carry out several processes such as editing techniques and reporting techniques. In addition, this journal also discusses the meaning, history of the emergence of radio and television. Radio is a form of mass media that is widely used by the public to access information. Radio was first discovered by Marconi in 1896. Initially radio served as a tool to convey information and news or for the benefit of the state in general. Public or commercial radio only appeared in the 1920s. Since then it has developed rapidly. Television comes from 2 (two) words, namely tele (Greek) which means far away, and vision (Latin) which means image / image. So as a whole, television can be interpreted as a system of presenting images along with sound from a place that is far away. In Indonesia, television was first introduced in 1962, when Indonesia had the honor to host the Asian Games Games in Jakarta. Radio and television together present information covered by reporters who bring news and information. The information conveyed must be precise and accurate in accordance with the events at the place where the information originates. The most important thing that must be considered by the person in charge of coverage in sorting out the coverage agenda is the news value.